2018
DOI: 10.1186/s40644-018-0161-9
|View full text |Cite
|
Sign up to set email alerts
|

Gastric heterotopic pancreas and stromal tumors smaller than 3 cm in diameter: clinical and computed tomography findings

Abstract: BackgroundIdentifying gastric heterotopic pancreas and stromal tumors is difficult. Few studies have reported computed tomography (CT) findings for differentiating lesions less than 3 cm in diameter. In this study, we aimed to identify clinical characteristics and CT findings that can differentiate gastric heterotopic pancreatic lesions from stromal tumors less than 3 cm in diameter.MethodsA total of 132 patients with pathologically confirmed gastric heterotopic pancreas (n = 66) and stromal tumors (n = 66) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…c, d Axial enhanced CT images of a heterotopic pancreas in the gastric antrum of a 58-year-old male showed a 1.2 cm × 0.8 cm, oval, ill-defined, and endoluminal lesion (white arrows), with a long diameter to short diameter > 1.4 lesion to aorta ratio method, but also combined significant variables in univariate analysis and achieved higher area under the curve values. Liu et al [41] and Li et al [32] both focused on the differentiation of gastric HP from gastric stromal tumors (GST); they have some differences and emphases. Liu et al [41] collected all GST in their study with a diameter limitation of ≥ 1 cm and calculated the CT attenuation disparities by using the enhanced CT attenuation value minus that of unenhanced phase while Li et al [32] limited the lesion diameter of < 3 cm, utilized stratified random sampling method to rate same sample sizes of gastric HP and GST, and employed the group validation method to prove the drawn conclusion of the primary cohort.…”
Section: Contrast-enhanced Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…c, d Axial enhanced CT images of a heterotopic pancreas in the gastric antrum of a 58-year-old male showed a 1.2 cm × 0.8 cm, oval, ill-defined, and endoluminal lesion (white arrows), with a long diameter to short diameter > 1.4 lesion to aorta ratio method, but also combined significant variables in univariate analysis and achieved higher area under the curve values. Liu et al [41] and Li et al [32] both focused on the differentiation of gastric HP from gastric stromal tumors (GST); they have some differences and emphases. Liu et al [41] collected all GST in their study with a diameter limitation of ≥ 1 cm and calculated the CT attenuation disparities by using the enhanced CT attenuation value minus that of unenhanced phase while Li et al [32] limited the lesion diameter of < 3 cm, utilized stratified random sampling method to rate same sample sizes of gastric HP and GST, and employed the group validation method to prove the drawn conclusion of the primary cohort.…”
Section: Contrast-enhanced Computed Tomographymentioning
confidence: 99%
“…GHP often presents as an intramural oval mass with indistinct margins on CT coronal images [ 23 , 30 ]. GHP is usually small in diameter (often less than 3 cm) and tends to be an intraluminal growth pattern [ 6 , 14 , 31 , 32 ]. The CT attenuation, enhancement heterogeneity, and enhancement degree of GHP correlate with its pathological histological compositions [ 5 , 9 , 10 , 14 , 23 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their large series studies, Zhang et al [ 15 ] and Betzler et al [ 16 ] reported that almost 85% of heterotopic pancreas cases were diagnosed incidentally. On the other hand, heterotopic pancreas was symptomatic in 35% and 100% of patients in other studies [ 17 - 19 ], respectively. The most common presenting symptom in the previously mentioned studies was abdominal pain (23-50%).…”
Section: To the Editormentioning
confidence: 81%
“…Currently, there are some limitations in diagnosing gastric EP. The imaging examination such as computed tomography and barium meal seems not very helpful in the diagnosis of gastric EP [19]. Pathological diagnosis is the gold standard.…”
Section: Discussionmentioning
confidence: 99%